Vegetable Handling, Distribution, and Wholesale Profitability in “Abinchi” Night Market, Kumasi-Ghana - Zu, K S A; Wongnaa, C A; Appiah, F (Journal of Postharvest Technology, 2014)
The study was conducted on vegetable handling practices, distribution and  wholesale haulage profitability in Abinchi night market Kumasi, Ghana. Focus  group discussions were held for middlemen, market queens and men, and 150  market queens and men were randomly selected and interviewed to elicit  prevailing handling practices. SPSS was used to analyze data obtained and  financial analytical tools; profit margin, return on investment and benefit cost  ratio were used to assess the profitability of the vegetable wholesale haulage.  Open and closed trucks, mini vans and taxis were identified to be regular  modes of transport of vegetables. Vegetables are packed and stored in jute  sacks with shelf life ranging from 3 to 7 days with visible deterioration over  days. The wholesale haulage of vegetable was viable in the months of July,  August and September. In mid September 2013, a 150 Kg sack full of cabbage  in Tepa, a major hub of vegetable production in the Ashanti region was selling  for an average of GH¢15 on farm. This constitutes 39% of the total cost of a  sack full of cabbage with about 61% constituting the cost of overheads and  transportation at the wholesale centre.
Keywords: Handling practices; Shelf life; Wholesale haulage; Profitability; Vegetables; Ghana